Rethinking Indonesia's Response to the Sino-U.S. Competition through the Lens of Constructivism - Naqsabandiyah, Ayu Heryati (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2023)
The emergence of China as a major power in the world has provoked turmoil among countries, particularly in the Asia-Pacific region. This situation was then responded to by the Western major powers, especially the United States and the United Kingdom, which carried out various maneuvers to counter China. Facing this situation, Indonesia has consistently conducted a middle-ground policy by not siding with one of the conflicting parties. Some scholars name this policy as a hedging strategy. Notwithstanding, existing research limits the explanations of the economic and security factors influencing Indonesia's position while overlooking non-material aspects. Against this background, this article seeks to fill this gap by analyzing Indonesia’s policy using the constructivist approach and explanatory qualitative research method. This research found three ideational aspects that shape the Indonesian government in issuing foreign policies related to major power competition in the Asia-Pacific, namely principles, values, and state identity. The concerned values and principles highlight that Indonesia adheres to Pancasila and “free and active” foreign policy principles which are primarily influenced by past colonialization and the struggle for independence. Meanwhile, identity refers to the international situation in which Indonesia has been exercising a vital role as the leader of global south countries. Keywords: China, constructivism, hedging strategy, Indonesia, the United States